Disparities in direct acting antivirals uptake in HIV‐hepatitis C co‐infected populations in Canada - Saeed, Sahar (J Int AIDS Soc, 2017)
BACKGROUND: Direct acting antivirals (DAAs) have revolutionized hepatitis C (HCV) treatment with >90% cure rates even in real‐world studies, giving hope that HCV can be eliminated. However, for DAAs to have a population‐level impact on the burden of HCV disease, treatment uptake needs to be expanded. We investigated temporal trends in HCV treatment uptake and evaluated factors associated with second‐generation DAA initiation and efficacy among key HIV‐HCV co‐infected populations in Canada. METHODS: The Canadian HIV‐HCV Co‐Infection Cohort Study prospectively follows 1699 participants from 18 centres. Among HCV RNA+ participants, we determined the incidence of HCV treatment initiation per year overall and by key populations between 2007 and 2015. Key populations were based on World Health Organization (WHO) guidelines including: people who actively inject drugs (PWID) (reporting injection drug use, last 6 months); Indigenous people; women and men who have sex with men (MSM). Multivariate Cox models were used to estimate adjusted hazard ratios (aHR) and 2‐year probability of initiating second‐generation DAAs for each of the key populations. RESULTS: Overall, HCV treatment initiation rates increased from 8 (95% CI, 6–11) /100 person‐years in 2013 to 28 (95% CI, 23–33) /100 person‐years in 2015. Among 911 HCV RNA + participants, there were 202 second‐generation DAA initiations (93% with interferon‐free regimens). After adjustment (aHR, 95% CI), active PWID (0.60, 0.38–0.94 compared to people not injecting drugs) and more generally, people with lower income (<$18 000 CAD/year) (0.50, 0.35, 0.71) were less likely to initiate treatment. Conversely, MSM were more likely to initiate 1.95 (1.33, 2.86) compared to heterosexual men. In our cohort, the population profile with the lowest 2‐year probability of initiating DAAs was Indigenous, women who inject drugs (5%, 95% CI 3–8%). Not having any of these risk factors resulted in a 35% (95% CI 32–38%) probability of initiating DAA treatment. Sustained virologic response (SVR) rates were >82% in all key populations. CONCLUSION: While treatment uptake has increased with the availability of second‐generation DAAs, marginalized populations, already engaged in care, are still failing to access treatment. Targeted strategies to address barriers are needed to avoid further health inequities and to maximize the public health impact of DAAs.